Design, synthesis and biological evaluation of a pseudo natural product compound collection - Yildirim, Okan (Technische Universität Dortmund, 2021)
Natural product (NP) scaffolds are valuable starting points for the design and synthesis of novel bioactive compounds as employed in biology-oriented synthesis (BIOS). However, the exploration of chemical and biological space by this method is limited by the guiding NPs. Combining NP fragments in an unprecedented not accessible by current biosynthetic pathways could enable the discovery of novel chemical and biological space. Compound classes obtained by the de novo combination of unrelated NP-derived fragments are called pseudo natural products (pseudo NPs). Based on the concept of synthesis of pseudo NP compound libraries, an enantioselective double 1,3-dipolar cycloaddition was applied to cyclopentadienones to combine two pyrrolidine fragments in an unprecedented manner (Chapter 3). Highly complex tricyclic molecules with up to eight stereocenters were obtained, including a quaternary center. Detailed mechanistic studies revealed that the double cycloaddition proceeds via an enantioselective dynamic covalent process. In dynamic covalent chemistry (DCC) the reaction follows a thermodynamically controlled pathway in an equilibrium process, allowing the interconversion of products. Time-dependent analysis showed kinetically controlled and thermodynamically favored product formation and an enantioselective interconversion of stereoisomers. Conditions for the selective synthesis of thermodynamically and kinetically controlled structurally complex double cycloadducts with high stereoselectivity from a common set of reagents were developed. Furthermore, a pseudo NP compound library was designed by combining the pyrrolidine scaffold with pyrroloindoline, generating a highly complex polycyclic compound class (Chapter 4). A synthetic strategy was designed employing an asymmetric 1,3-dipolar cycloaddition, indole formation and dearomatization. Excellent diastereoselectivity was achieved through a substrate controlled cyclization process.

Naturstoff-Grundgerüste sind wertvolle Ausgangspunkte für das Strukturdesign und die Synthese von neuen bioaktiven Verbindungen, wie bereits in der Biologie orientierten Synthese (BIOS) durchgeführt. Die Untersuchung des chemischen und des biologischen Raums ist jedoch von der Wahl des Naturstoffes eingeschränkt. Die Kombination von Naturstofffragmenten in neuartiger Weise, welche über biosynthetische Wege unzugänglich ist, könnte die Entdeckung von neuen chemischen und biologischen Räumen ermöglichen. Verbindungsklassen, welche durch Kombination von nicht miteinander verwandten Naturstofffragment erhalten werden, werden als Pseudo-Naturstoffe bezeichnet. Für die der Synthese von Bibliotheken von Pseudo-Naturstoffen wurde eine enantioselektive doppelte Cycloaddition an Cyclopentadienon durchgeführt, welche eine neuartige Kombination von Pyrrolidin-Fragmenten ermöglichte (Kapitel 3). Hochkomplexe trizyklische Moleküle mit bis zu acht Stereozentren wurden erhalten, wobei eines der Stereozentren ein quaternäres Zentrum ist. Intensive mechanistische Untersuchungen zeigten, dass die doppelte Cycloaddition durch einen dynamischen kovalenten Prozess abläuft. In der dynamischen kovalenten Chemie folgt die Reaktion einem thermodynamisch kontrollierten Reaktionsverlauf in einem Gleichgewichtsprozess, in welcher die Produkte umgewandelt werden. Eine zeitabhängige Analyse zeigte die Bildung von kinetisch und thermodynamisch kontrollierten Reaktionsprodukten und eine enantioselektive Umwandlung der jeweiligen Stereoisomere. Des Weiteren wurden Reaktionsbedingungen für die selektive Synthese von sowohl kinetisch als auch thermodynamisch kontrollierten hochkomplexen Cycloadditions-Produkten mit hoher Stereoselektivität unter Anwendung von gleichen Reagenzien entwickelt. Des Weiteren wurde eine weitere Pseudo-Naturstoff-Substanzbibliothek durch Kombination von Pyrrolidin-Grundgerüsten mit Pyrroloindolin entwickelt, bei der polyzyklische Verbindungen erhalten wurden. Eine Synthesestrategie aus 1,3-dipolarer Cycloaddition, Indol-Bildung und anschließender Dearomatisierung wurde angewendet. Exzellente Diastereoselektivität wurde durch eine substrat-kontrollierte Zyklisierung erzielt.
Keywords: 1,3-dipolar cycloaddition; Dynamic covalent chemistry; Pseudo natural product; Stereodivergent synthesis; Dearomatization; 570; 540; Cycloaddition; Naturstoffchemie